In Vitro and In Vivo Antidiarrheal Activity of Dragon Fruit Peels Methanolic Extract - Stephanie Renata Yosefa; Erny Tandanu; William Leslie; Silvia Fransisca; Evelyn Angie; Djamin Kartarino; Refi Ikhtiari (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Diarrhea is a global major health problem reported by 2.5 billion cases annually. Diarrhea accounts for 9% of child death worldwide or the second leading cause of death among toddlers. Many local people have used traditional medicine for diarrhea therapy. Dragon fruit is a herbal plant with high vitamins and various nutritious compounds. Therefore, this study determined antidiarrheal activity from dragon fruit peel methanolic extract (Hylocereus polyrhizus). This study was experimental with in vitro and in vivo models. The in vitro model used disc diffusion and microdilution assay against the diarrhea-causing pathogen (Escherichia coli). Meanwhile, the in vivo model used male Wistar rats induced by Castro oil. This study showed that the minimum inhibitory concentration (MIC) and minimum killing concentration (MKC) of dragon fruit peel extract against Escherichia coli were 50 and 100 mg/ml, respectively. The increased dose of dragon fruit peel methanol extract has increased the antidiarrheal index. The highest and lowest antidiarrheal index was found in the dragon fruit methanol extract-3 (76.56%) and dragon fruit methanol extract-1 (43.28%). The dragon fruit peel methanol extract can be proposed as antidiarrhea and antibacterial therapy against the diarrhea-causing pathogen.